Kinerja Implementor Program Penyediaan Air Minum Dan Sanitasi Berbasis Masyarakat (PASIMAS) Di Kabupaten Sinjai - Rudianto, Rudianto; Madani, Muhlis; Nasrulhaq, Nasrulhaq (Universitas Muhammadiyah Makassar, 2021)
This study purposed to find out the performance of community-based water supply and sanitation (Pamsimas) implementers in Sinjai District. The method of this study used descriptive qualitative with type of phenomenological research. The number of informants in this study were 6 people. Data Sources used primary data and secondary data, data analysis techniques with data reduction, data presentation and verification. The validation of the data used source triangulation, technical triangulation, and time triangulation. The results of this study showed that the Performance of the Community Based Water Supply and Sanitation (Pamsimas) Implementersin Sinjai Regency were used as benchmarks namely productivity, service quality, cost and customer satisfaction . There were four factors that had run optimally and in accordance with applicable laws and government regulations.